2014
DOI: 10.1553/populationyearbook2013s295
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of exceptional human longevity: new ideas and findings

Abstract: Studies of centenarians are useful in identifying factors leading to long life and avoidance of fatal diseases. In this article we consider several approaches to study effects of early-life and midlife conditions on survival to advanced ages: use of non-biological relatives as controls, the within-family analysis, as well as a sampling of controls from the same population universe as centenarians. These approaches are illustrated using data on American centenarians, their relatives and unrelated shorterlived c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 93 publications
(113 reference statements)
0
11
0
Order By: Relevance
“…The main focus of the study is on the 1900 and 1930 censuses that correspond to the childhood and adulthood periods of their individual lives. The age at death for controls is selected assuming that the majority of deaths at age 65 occur due to chronic age-related diseases rather than injuries or infectious diseases (Gavrilov and Gavrilova 2013). This design does not suffer from so-called immortal time bias (Ferrie and Ebrahim 2014) because we analyzed past events and conditions when both cases and controls were alive (and of the same age) and did not analyze variables collected at time of death for centenarians and shorter-lived controls.…”
Section: The Between-family Approach: Sampling Centenarians and Gementioning
confidence: 99%
“…The main focus of the study is on the 1900 and 1930 censuses that correspond to the childhood and adulthood periods of their individual lives. The age at death for controls is selected assuming that the majority of deaths at age 65 occur due to chronic age-related diseases rather than injuries or infectious diseases (Gavrilov and Gavrilova 2013). This design does not suffer from so-called immortal time bias (Ferrie and Ebrahim 2014) because we analyzed past events and conditions when both cases and controls were alive (and of the same age) and did not analyze variables collected at time of death for centenarians and shorter-lived controls.…”
Section: The Between-family Approach: Sampling Centenarians and Gementioning
confidence: 99%
“…We found significant beneficial effects of a young maternal age at a person's birth on survival to age 100 with particularly strong positive influence at a maternal age of 20-24 years [25, 26, 32]. The effect of a young mother was particularly prominent in smaller families [25], which is pertinent today because of the smaller average family size in contemporary population (Figure 2). Thus, the within-family analysis of the paternal-and maternal-age effects on human longevity demonstrated that a young age of the mother increases the chances of children to reach longevity.…”
Section: Introductionmentioning
confidence: 92%
“…At the same time, early exposure to infections as estimated indirectly from child mortality in the families of cases and controls had no effect on longevity. Overall, childhood conditions reported in the 1900 census were not predictive for exceptional longevity for either men or women [24]. On the other hand, some early-life characteristics (birth in the northeastern part of the United States and birth in the second half of the year) turned out to be significant predictors of exceptional longevity (for men but not women).…”
Section: Biodemography Of Exceptional Longevitymentioning
confidence: 99%
See 1 more Smart Citation
“…Aging is a complex and heterogeneous process, which depends on genetic background and lifestyle [12]. Comparative analysis of twins' age of deaths [13,14] and pedigree studies with longevous families [15][16][17] showed a modest participation of heritability in life span, which favors environmental and lifestyle components [18]. Previous studies have estimated that 20-25% of healthy longevity may rely on our genes' variability and the remainder on the environment [18].…”
Section: Populational Aging Is One Of the Main Challenges Of Contempo...mentioning
confidence: 99%